ANALISIS PENENTUAN HARGA POKOK PRODUKSI RUMAH PADA CV. LIFERINDO GRAHA PRIMA SORONG - Kurniati, Erna; muda, Markus; Tefa, Margarita (Jurnal Pitis AKP, 2019)
Production costs are costs that are directly or indirectly related to the production process or the processing of materials to become a finished product. Production costs, namely, all costs associated with the production function or processing activities of raw materials into finished products, production costs are classified into raw material costs, direct labor material costs, and factory overhead costs. Liferindo is a company engaged in the contracting sector. The company's operational income comes from real estate development activities, namely the sale of houses and their plots of land. This study aims to determine the suitability of the determination of the cost of production carried out by the company with the applicable accounting principles.